Staffing methods for positions of sales representatives in selected companies - Bednaříková, Marie; Nožičková, Ivana; Vávra, Jan (University of Pardubice, 2012)
It is necessary for every company to find and to keep qualified and motivated employees for meeting the company goals. Recruitment and selection processes of appropriate sales representatives should be carried out extremely carefully. This paper deals with problem issues of recruitment and selection of sales representatives and is accompanied with a research having taken place in early 2012 and being focused on the methods of selecting them.